2023
DOI: 10.1099/mgen.0.000952
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis outbreak caused by an emerging zoonotic strain with acquired multi-drug resistance in Thailand

Abstract: Streptococcus suis is an emerging zoonotic swine pathogen which can cause severe infections in humans. In March 2021, an outbreak of S. suis infections with 19 confirmed cases of septicemia and meningitis leading to two deaths, occurred in Nakhon Ratchasima province, Thailand. We characterized the outbreak through an epidemiological investigation combined with Illumina and Nanopore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…S6). Most of them (except Ala460Val, Thr491Ser and Arg514Asp/Gly) have already been described previously in penicillin-resistant isolates of S. suis [45, 63–65]. Two modifications (Met144Ile/Leu/Thr and Val145Ile/Leu) were detected in the glycosyltransferase domain of MraY.…”
Section: Resultsmentioning
confidence: 81%
“…S6). Most of them (except Ala460Val, Thr491Ser and Arg514Asp/Gly) have already been described previously in penicillin-resistant isolates of S. suis [45, 63–65]. Two modifications (Met144Ile/Leu/Thr and Val145Ile/Leu) were detected in the glycosyltransferase domain of MraY.…”
Section: Resultsmentioning
confidence: 81%
“…The fourth outbreak was reported in Uttaradit province in May 2019, with 5 confirmed cases and 18 suspected cases [17]. A fifth outbreak occurred for the first time in northeastern Thailand (Nakhon Ratchasima) in 2021, with 21 confirmed cases, including 2 fatal cases [18]. Microbiological analysis of the outbreak S. suis strains showed that the first and second outbreaks were due to serotype 2 with sequence type (ST) 1, while the third outbreak was caused by serotype 2-ST104 and serotype 14-ST105.…”
Section: Epidemiology Of Human S Suis Infections In Thailandmentioning
confidence: 99%
“…There was no available information about the serotype and STs in the fourth outbreak. The fifth outbreak was caused by serotype 2 with a new ST (ST1656) belonging to the clonal complex (CC) 233/379 [18].…”
Section: Epidemiology Of Human S Suis Infections In Thailandmentioning
confidence: 99%
See 2 more Smart Citations